Immunological demonstration of the accumulation of insulin, but not insulin receptors, in nuclei of insulin-treated cells. - Soler, A P (1989)
Although insulin is known to regulate nuclear-related processes, such as cell growth and gene transcription, the mechanisms involved are poorly understood. Previous studies suggested that translocation of insulin or its receptor to cell nuclei might be involved in some of these processes. The present investigation demonstrated that intact insulin, but not the insulin receptor, accumulated in nuclei of insulin-treated cells. Cell fractionation studies demonstrated that the nuclear accumulation of 125I-labeled insulin was time-, temperature-, and insulin-concentration-dependent. Electron microscopic immunocytochemistry demonstrated that the insulin that accumulated in the nucleus was immunologically intact and associated with the heterochromatin. Only 1% of the 125I-labeled insulin extracted from isolated nuclei was eluted from a Sephadex G-50 column as 125I-labeled tyrosine. Plasma membrane insulin receptors were not detected in the nucleus by immuno electron microscopy or when wheat germ agglutinin-purified extracts of the nuclei were subjected to PAGE, electrotransfer, and immunoblotting with anti-insulin receptor antibodies. These results suggested that internalized insulin dissociated from its receptor and accumulated in the nucleus without its membrane receptor. We propose that some of insulin's effects on nuclear function may be caused by the translocation of the intact and biologically active hormone to the nucleus and its binding to nuclear components in the heterochromatin.